The Increase of Rural Economy at Baraka Sub-District through Village Funds - Abdul Karim; Chalid Imran Musa; Romansyah Sahabuddin; Muhammad Azis (Bina Nusantara University, 2021)
The research aimed to examine the allocation of Village funds during the COVID-19 global crisis pandemic as well as its benefits to Baraka Sub-district in Enrekang Regency, South Sulawesi Province. It has an area of 159,15 km2 or 8,91% of the accumulated total area of Enrekang Regency. The research applied was qualitative method with a descriptive analysis approach. It is carried out by collecting data and information from the population taken from 12 villages in the Baraka Sub-district. The results show that BUMDes (Village-owned Enterprises) fosters rural economic development for all village communities in Baraka Sub-district and supports national economic growth. In addition, Village funds is considered to become a support for meeting the economic needs of the community during the COVID-19 pandemic. It is expected that various economic recovery programs will continue, whether they become central, regional, or local village-scale programs, especially in 12 villages in Baraka Sub-district.